An Analysis of the Canadian Christian Mission's Evangelistic Activities in the Chengdu Region During the Late Qing and Republican Periods Based on the En Guang Church - ZUO Yanan, (Journal of Research for Christianity in China (JRCC), 2025)
Chengdu's Grace Church was the first church constructed by the Canadian Anglo-American Mission after its arrival in Sichuan. It also served as Chengdu's primary Christian church, becoming a symbol of the mission's evangelistic activities in the Chengdu region. This paper takes Grace Church as its starting point. Through a brief account of its origins and development, drawing on relevant historical materials and field research, it focuses on examining the missionary activities of the Canadian Anglo-American Mission in Chengdu during this period, particularly in the field of healthcare. This approach aims to acknowledge the church's contributions to the progress of various aspects of society in the Chengdu region and to the exchange between Chinese and Western cultures.